Human Development and Political Violence - Daiute, Colette (Cambridge : Cambridge University Press, 2010)
Human Development and Political Violence presents an innovative approach to research and practice with young people growing up in the context of political violence. Based on developmental theory, this book explains and illustrates how children and youth interact with environments defined by war, armed conflict, and the aftermath involving displacement, poverty, political instability, and personal loss. The case study for this inquiry was a research workshop in four countries of the former Yugoslavia, where youth aged 12 to 27 participated in activities designed to promote their development. The theory-based Dynamic Story-Telling by Youth workshop engaged participants as social historians and critics sharing their experiences via narratives, evaluations of society, letters to public officials, debates, and collaborative inquiries. Analyses of these youth perspectives augment archival materials and researcher field notes to offer insights about developmental strategies for dealing with the threats and opportunities of war and major political change.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Youth and violence; Developmental psychology; Life cycle, Human